A De Novo Approach for the Stereoselective Synthesis of Cyclopenta[c]pyranone Scaffold Present in Iridoids: Formal Syntheses of Isoboonein, Iridomyrmecin and Isoiridomyrmecin. Issue 20 (28th May 2018) - Kaurav, Manvendra Singh; Kumar, Virendra; Kumar, Dileep; Khan, Tabrez
Abstract: A conceptually new intramolecular Pauson‐Khand reaction (IPKR) based general strategy has been demonstrated for the formal syntheses of isoboonein, iridomyrmecin and isoiridomyrmecin from very cheap, commercially available starting material. Abstract : A new and efficient racemic route employing an intramolecular Pauson‐Khand reaction as the key step for stereoselective construction of the cyclopenta[c]pyran‐3‐one scaffold present in iridoid class of natural products is described, starting from a very cheap, commercially available starting material. Further, the scope of approach for the formal syntheses of isoboonein, iridomyrmecin and isoiridomyrmecin has been demonstrated.